Precious metal enrichment at low-redox in terrestrial native Fe-bearing basalts investigated using laser-ablation ICP-MS. (15th April 2017) - Howarth, Geoffrey H.; Day, James M.D.; Pernet-Fisher, John F.; Goodrich, Cyrena A.; Pearson, D. Graham; Luo, Yan; Ryabov, Viktor V.; Taylor, Lawrence A.
Abstract: Primary native Fe is a rare crystallizing phase from terrestrial basaltic magmas, requiring highly reducing conditions ( f O2 <iron-wüstite buffer) in order to form. Reducing conditions in basaltic magmas can be achieved through assimilation of carbonaceous crustal material, which leads to formation of an immiscible, molten, C-rich, native Fe alloy liquid. If this liquid also contains sufficient sulfur, it can undergo further division into conjugate Fe–C-rich and a Fe–S-rich immiscible melts that can effectively scavenge the highly siderophile elements (HSE: Re, Au, and the platinum group elements [PGE], Pd, Pt, Rh, Ru, Ir, Os), as well as Ni and Cu, to economic abundances. Three localities are known globally where native Fe bearing mafic rocks occur: (1) Paleocene basalts of Disko Island, West Greenland; (2) a Miocene lava of the Bühl basalts, Germany; and (3) mafic intrusions associated with the Late Permian Siberian flood basalts. In this contribution, we report major- and minor-element compositions and HSE concentrations for the main alloy phases (FeNi metal and cohenite) and sulfide, for all three known global occurrences of native Fe bearing basalt. Total HSE abundances in metal grains, obtained by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), are lowest in the Bühl basalt, (∼0.05 ppm), intermediate in the Disko Island basalts (4–8 ppm), and highest the Siberian Khungtukun and Dzhaltul intrusions (10–30 ppm). These differences demonstrate that, while native Fe formation is the result of carbonaceous crustal assimilation, HSE enrichment is not ubiquitous during this process. The Siberian occurrences are characterized by Pt PGE (PPGE: Pt, Pd) enrichment relative to the Ir PGE (IPGE: Rh, Ru, Ir, Os), consistent with models of early stage fractionation of olivine, chromite and metallic IPGE in staging magma reservoirs, prior to the addition of C-rich crustal materials in the shallow crust. Relative to Noril'sk Ni–Cu-PGE sulfide ores, the Siberian native Fe basalts are enriched in the PPGE relative to the IPGE, but exhibit Ru enrichments. In contrast, Disko Island native Fe rocks do not show significant fractionation of the PPGE from the IPGE, but have positive Re and Ru anomalies and high Os/Ir ratios. To reconcile these observations, we present a general model where some parental melts experienced early-stage crustal assimilation in staging magma reservoirs, prior to reduction by carbon-rich materials (e.g., Khungtukun, Dzhaltul), whereas basaltic parental melts to Disko Island and Bühl solely experienced interaction with carbonaceous material, resulting in extensive devolatilization, native Fe segregation, and native Fe formation.